Job Satisfaction, Training & Development and Work Environment on Career Adaptability Among Fresh Graduates In Malaysia - Nursyafiah Bt Mohammad, Amira; Hanie Abu Samah, Irza; ., Saraih; Naiemah, Ummi; Maizura Abd Rashid, Intan; Nurshahrizleen, Sayang; Hassan Basri, Haslina; Fitri Mansor, Mohd (International Journal of Engineering and Technology, 2018)
In Malaysia, there is a profusion evidence of high graduatesâ€™ unemployment since many graduates are found lacking of what are needed to acquire and to maintain their jobs. This study explored career adaptability would have influence on intention to leave the organization and their career. Data collected in a standardized manner through simple random sampling via survey questionnaire. 247 sets of answer questionnaire were collected back from the respondents where they were have working experiences for at least one year. This research applied a quantitative method. Using SPSS, Pearson correlation and regression were used to determine the factors that most influence on career adaptability. Finding in this study reveals that there is moderate relationship between independent variables and dependent variable whereby correlation between job satisfaction and career adaptability the result is (r-value= 0.212, p<0.01). Second correlation is the relationship between training and development, the result show that r-value= 0.293 (p <0.01). finally, for correlation between working environment and career adaptability which is r-value = 0.222 (p <0.01). Gaining this information, organization can have used them to monitor the turnover rate in the company especially among younger generation. It is well known that graduates being hired is the best one, and also it becomes a challenge for organization to retain best employees.Â